PEMBERDAYAAN PETANI MELALUI PEMBUATAN PUPUK ORGANIK PADAT DARI KOTORAN SAPI UNTUK MEMINIMALISIR PENGGUNAAN PUPUK KIMIA - Puspaningrum, Diah; Putra, Ryan Rhesa; Mafinanik, Aliza Febrianti; Fadilah, Nisful Nur (PAPUMA: Journal of Community Services, 2025)
The agricultural sector has a very important role in meeting people’s food needs an as a driver of the Indonesian economy. Agriculture that relies on chemical fertilizers in crop cultivation can cause damage to the soil and the environment. The use of organic fertilizer is highly recommended as an environmentally friendly alternative. Organic fertilizer is one good solution, namely by using cow dung waste as the main ingredient for making solid organic fertilizer. Professional internship activities in Paguan village, Taman Krocok District, Bondowoso Regency, aim to provide training in making solid organic fertilizer from cow dung. The stages carried out in this activity include socialization and practice of making organic fertilizer made from cow dung. The method use in this activity is Participatory Rural Appraisal (PRA), which aims to increase public awareness and trust in making solid organic fertilizer from cow dung. The empowerment carried out in this method is enabling, strengthening, protecting, supporting, and maintaining. his activity is expected to improve human resources in the form of understanding and ability of Farmer Groups in managing natural resources sustainably and reducing dependence on using chemical fertilizers. Farmers are also able to make organic fertilizer from cow manure to reduce dependence on the use of chemical fertilizers.